2014
DOI: 10.3109/07388551.2014.899964
|View full text |Cite
|
Sign up to set email alerts
|

Current developments in arbuscular mycorrhizal fungi research and its role in salinity stress alleviation: a biotechnological perspective

Abstract: Arbuscular mycorrhizal fungi (AMF) form widespread symbiotic associations with 80% of known land plants. They play a major role in plant nutrition, growth, water absorption, nutrient cycling and protection from pathogens, and as a result, contribute to ecosystem processes. Salinity stress conditions undoubtedly limit plant productivity and, therefore, the role of AMF as a biological tool for improving plant salt stress tolerance, is gaining economic importance worldwide. However, this approach requires a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 190 publications
0
40
0
3
Order By: Relevance
“…The substrate conditions in the three sites analyzed in the present study are considered hypersaline (FAO 1994) and can cause damage through the toxicity of the ions themselves or by osmotic stress to both the plants and the AMF (Juniper & Abbott 2006, Munns & Tester 2008, Evelin et al 2009). However, it has been reported that the AMF are capable of providing benefits to their hosts in conditions of elevated salinity (Kumar et al 2015). In this study, arbuscules were recorded within the roots of C. erectus in all three sites, indicating that the association is functional (Espinosa-Victoria 2000) under the entire range of salinities analyzed.…”
Section: Discussionmentioning
confidence: 46%
“…The substrate conditions in the three sites analyzed in the present study are considered hypersaline (FAO 1994) and can cause damage through the toxicity of the ions themselves or by osmotic stress to both the plants and the AMF (Juniper & Abbott 2006, Munns & Tester 2008, Evelin et al 2009). However, it has been reported that the AMF are capable of providing benefits to their hosts in conditions of elevated salinity (Kumar et al 2015). In this study, arbuscules were recorded within the roots of C. erectus in all three sites, indicating that the association is functional (Espinosa-Victoria 2000) under the entire range of salinities analyzed.…”
Section: Discussionmentioning
confidence: 46%
“…AMF symbiosis has been found to enhance salinity tolerance in different host plants, such as cucumber, lettuce, tomato, maize, acacia and citrus [32][33][34][35][36][37]. AMF increase absorption of soil water through the mycelium and mobilization in the plant, enhance soil-root contact, reduce the deleterious effects of phytotoxic ions on the integrity of the plasmatic membrane and cell organelles, change phytohormone balance, increase antioxidant defenses (both enzymatic and non-enzymatic) and promote the expression of salt stress-related genes [37][38][39][40][41]. In addition, AMF may increase root hydraulic conductivity at low water potential [42], promote and change root system architecture, and enhance stomatal conductance by improving the gas exchange capacity [31,37,39,43].…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%
“…Algunas investigaciones se han referido a la importancia que la simbiosis AMF-planta ha tenido en los sistemas agroproductivos debido al cúmulo de evidencias que han permitido constatar beneficios en las especies hospedantes (Field et al, 2015) tales como conferir tolerancia a la sequía (Ortiz et al, 2015), salinidad (Kumar et al, 2015a;Dar et al, 2018) -Dzul et al, 2011;Preciado et al, 2011).…”
Section: Dentro De Los Géneros De Bpcv Más Importantesunclassified